A synthetic genomics-based African swine fever virus engineering platform - Fuchs, W.; Assad-Garcia, N.; Abkallo, Hussein M.; Xue, Y.; Oldfield, L.M.; Fedorova, N.; Hübner, A.; Kabuuka, T.; Pannhorst, K.; Höper, D.; Nene, Vishvanath; Gonzalez-Juarbe, N.; et al. (American Association for the Advancement of Science, 2025)
African swine fever (ASF) is a deadly viral disease in domestic pigs that has a large global economic impact for the swine industry. It is present in Africa, Europe, Asia, and in the Caribbean island of Hispaniola. There are no effective treatments or broadly licensed vaccines to prevent disease. Efforts to counteract ASF have been hampered because of the lack of convenient tools to engineer its etiological agent, ASF virus (ASFV), largely due to its large noninfectious genome. Here, we report the use of synthetic genomics methodology to develop a reverse genetics system for ASFV using a CRISPR-Cas9–inhibited self-helper virus to reconstitute live recombinant ASFV from synthetic genomes to rapidly generate a variety of combinatorial mutants of ASFV. The method will substantially facilitate the development of therapeutics or subunit and live-attenuated vaccines for ASF. This synthetic genomics-based approach has wide-ranging impact because it can be applied to rapidly develop reverse genetics tools for emerging viruses with noninfectious genomes.